Hedging costs and joint determinants of premiums and spreads in structured financial products - Oliver Entrop; Georg Fischer (Journal of Futures Markets, 2020)
Evaluating more than 317,000 discount certificates in the German secondary market, we find that premiums and spreads are endogenous and negatively related but depend on different key determinants. The fundamental determinants of the premiums are mainly profit-related, that is, dividends of the underlying, issuers' credit risk, lifecycle effect, and competition, whereas hedging costs are less important. However, initial hedging costs (IHC) are priced into the premium in the case of large inventory changes. The spread is mostly determined by hedging costs and risk components, such as IHCs, rebalancing costs, volatility, scalper risk, and overnight gap risk—but also by dividends.
Keywords: 330; derivatives; discount certificates; hedging; market microstructure; pricing; trading costs